An investigation of influencing of Sb and Bi contents on surface tensions associated with Pb-free Sn-Zn-Sb-Bi quaternary and sub-quaternary solder alloys. Issue 15 (3rd August 2019) - Dogan, Ali; Arslan, Hüseyin
ABSTRACT: The surface tensions of ternary and quaternary systems of Sn-based Pb-free solder alloys have been calculated using geometric models, such as Muggianu, Kohler, Chou's general solution model (GSM), Toop, Guggenheim, ideal Butler and Butler models. It is observed from the calculation carried out in the present work that Sb and Bi contents decrease the surface tension of the solder alloys Sn-Zn-Sb-Bi. It is inferred from the statistical analysis that the best agreement between the experimental results and the corresponding calculated values of the surface tensions is generally observed in GSM and Muggianu models among the geometric models. Whereas Muggianu model is the most appropriate. Relatively good agreements have been observed between models considered in this study and experimental data.